Nanocomposites of TiO2 and Reduced Graphene Oxide as Efficient Photocatalysts for Hydrogen Evolution - Fan, Wenqing; Lai, Qinghua; Zhang, Qinghong; Wang, Ye (Journal of physical chemistry. C, 2011)
Nanocomposites of titanium dioxide (P25) and reduced graphene oxide (RGO), which were prepared by several techniques including UV-assisted photocatalytic reduction, hydrazine reduction, and hydrothermal method, were studied as photocatalysts for the evolution of hydrogen from alcohol solution under UV–vis irradiation. The incorporation of RGO into P25 significantly enhanced the photocatalytic activity for H2 evolution, and the P25–RGO composite prepared by the hydrothermal method exhibited the best performance. The optimum mass ratio of P25 to RGO in the composite was 1/0.2. The P25–RGO composite was stable and could be used recyclably, and it could also catalyze the evolution of H2 from pure water. Our characterizations suggested that P25 nanoparticles with diameters of 20–30 nm were dispersed on the RGO sheet in the composite, and the stronger interaction between P25 and RGO provided a better photocatalytic activity. The intimate contact between P25 and RGO was proposed to accelerate the transfer of photogenerated electrons on P25 to RGO, suppressing the recombination of charge carriers and thus increasing the photocatalytic performance.